Value Awareness: A New Goal for End-of-life Decision Making. Issue 1 (February 2019) - Fischhoff, Baruch; Barnato, Amber E.
The principal policy tool for respecting the preferences of patients facing serious illnesses that can prompt decisions regarding end-of-life care is the advance directive (AD) for health care. AD policies, decision aids for facilitating ADs, and clinical processes for interpreting ADs all treat patients as rational actors who will make appropriate choices, if provided relevant information. We review barriers to following this model, leading us to propose replacing the goal of rational choice with that of value awareness, enabling patients (and, where appropriate, their surrogates) to be as rational as they can and want to be when making these fateful choices. We propose approaches, and supporting research, suited to individuals' cognitive, affective, and social circumstances, resources, and desires.